A father's law - Wright, Richard 1908-1960 (Harper Perennial, 2008)
A novel left unfinished by Richard Wright at the time of his death in 1960, telling the story of Ruddy Turner, an African-American police chief in a Chicago suburb, who struggles to know what to do when he begins to suspect his college-age son Tommy is a murderer.
Keywords: African American police chiefs -- Fiction; Fathers and sons -- Fiction; Conflict of generations -- Fiction; Psychological fiction; Suspense fiction